Analysis of REITs listed on SGX (retail, hospitality, healthcare, data centre) - Law, Lionel Jian Ping (Nanyang Technological University, 2022)
In this paper, we will analyze the performance of Singapore Real Estate Investment Trusts (S-REITs) and Business Trust through two research areas. Firstly, we identify key financial metrics and use correlation analysis to determine the metric most correlates with price movement and dividend payout. We find that net asset value (NAV) is the metric most related to the price movement and dividend payout, and we rank the S-REITs performance using an average quarter to quarter growth on NAV. Secondly, we determine the share price movement of the S-REIT when it trades ex-dividend or when there is an unprecedented news surface.